Pengambilan Keputusan (Decision Making) Untuk Total Quality Management In Education (TQME) di Tengah Tantangan Global - Sauqi Futaqi (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2019)
The purpose of this study discusses decision making used in the application of total quality management in Education (TQME). The decisions taken in TQME have different characteristics, because its priority is customer satisfaction. Therefore, decisions need to consider the global challenges, because it’s as well as sufficient influence customer needs and interests of educational services. The decision-making for TQME must consideration that is always be responsive and contextual appropriate with an indicator of customer satisfaction.